Size Firm and Capital Structure Against Earnings Management of Islamic Banks Listed on The Indonesia Stock Exchange - Muh Syahrullah Ramadhan (Business Finance Analyst Co., 2023)
This study aims to provide empirical evidence related to firm size and capital structure on earnings management. Company size is obtained by the natural logarithm of assets, and capital structure is measured using the debt-equity ratio. Meanwhile, in measuring the value of earnings management using discretionary accruals and calculated using the modified Jones model. The samples used in this study were 4 Islamic banks listed on the (IDX). The observation period was 2021-2022, using secondary data in the form of quarterly financial reports. The data analysis technique used is panel data regression on Eviews 9 software. Based on the test results, it is found that company size individually affects earnings management, and capital structure has no effect on earnings management.